JHEA, Volume 17, n° 1 & 2, 2019 - Full Issue - Journal System (Journal of Higher Education in Africa, 2021)
Contents Re-imagining Leadership Development for Middle-level Academic Leaders in Africa Oliver Seale..........................................................................................1 Academic Programme Leadership in African Higher Education: A Phenomenological Reflection Lester Brian Shawa.........................................................................27 Leadership Development Schemes for Middle-level Academics in Merged Universities: The Case of Kyambogo University George Wilson Kasule.....................................................................43 The Culture of Middle-level Academic Management at a Comprehensive South African University George Mavunga............................................................................63 Junior Academics within Middle Level Academic Leadership in Emerging Universities in Nigeria Babatunde Joshua Omotosho..........................................................83 Roles, Stress and Coping Mechanisms among Middle-level Academic Leaders in Multi-campus Universities in Africa Dennis Zami Atibuni...............................................................................95